Salary perception and career prospects in audit firms. Issue 6 (29th May 2020) - Hammami, Ahmad; Moldovan, Rucsandra; Peltier, Elisabeth
Abstract : Purpose: This paper aims to examine the role that auditor's salary perception has on audit quality and delay. The findings contribute to a greater understanding of the audit employee-level factors that influence audit work outcomes. Design/methodology/approach: The authors use Big 6 employee reviews, salary data and audit and financial data from 2007 to 2017 to measure how to audit employees' pay satisfaction affects audit quality (small profits and going concern opinions) and audit delay. The authors use a regression approach to analyze this relationship. In subsequent tests, the authors split the sample on high career opportunities to investigate how this moderates the relationship between salary perception and audit quality. Findings: The authors document a discrepancy between pay perception and reality. It is explained, though not completely, by salary level, comparisons to peers and superiors, firm-wide attitudes, cost of living and human capital in the area, work–life balance and perceived career prospects. Surprisingly, the unexplained pay dissatisfaction relates positively to audit quality and audit efficiency (audit delay), after controlling for salary level. Further tests show that an audit employee's expectation of career opportunities moderates this result. Originality/value: This is the first paper that empirically tests the relationship between pay satisfaction and job performance in the context of audit employees in public accounting. The authors contribute to an emerging literature that investigates audit employee-level characteristics and attitudes in relation to audit quality.